Efficacy of a non-invasive model in predicting the cardiovascular morbidity and histological severity in non-alcoholic fatty liver disease. Issue 3 (May 2019) - Hanafy, Amr Shaaban; Seleem, Waseem M.; El-kalla, Ferial; AbdAlkhalik Basha, Mohammad; Abd-Elsalam, Sherief
Abstract: Background: Insulin resistance (IR) in cases of non-alcoholic fatty liver disease (NAFLD) is connected to remarkable liver cell inflammation and cardiovascular complications. Given the prevalence of NAFLD and its association with potential sequels, there is a strong need for an accurate non-invasive tool to monitor the progression of NAFLD. Methods: 272 patients with NAFLD and cardio-metabolic risk factors were tested for HOMA-IR, mean platelet volume (MPV), neutrophil-lymphocyte ratio (NLR), uric acid, ferritin, lipid profile, liver stiffness measurement (LSM), controlled attenuation parameter (CAP) by fibroscan and carotid intima media thickness (CIMT). Liver biopsy was performed to validate the results.100 healthy controls were selected. A score was constructed and applied to a validation group (n = 61). Results: Logistic regression revealed that significant fibrosis and cardiovascular risk in NAFLD were independently associated with AST/ALT ratio (p = 0.000), GGT (p = 0.000), CIMT (p = 0.001), uric acid (p = 0.000), VLDL (p = 0.000), HOMA-IR (p = 0.000), ferritin (p = 0.000) CAP (p = 0.000), LSM (p0.000). A non-invasive model was formulated by which a value > 15 was accurate in identification of advanced fibrosis and cardiovascular risk with a sensitivity of 97.3%, specificity 97%. Conclusion: The score correlated well with the results of liver biopsy and can be repeated with great flexibility to assess severity of NAFLD.